2023
DOI: 10.1213/ane.0000000000006395
|View full text |Cite
|
Sign up to set email alerts
|

Society of Anesthesia and Sleep Medicine Position Paper on Patient Sleep During Hospitalization

Abstract: This article addresses the issue of patient sleep during hospitalization, which the Society of Anesthesia and Sleep Medicine believes merits wider consideration by health authorities than it has received to date. Adequate sleep is fundamental to health and well-being, and insufficiencies in its duration, quality, or timing have adverse effects that are acutely evident. These include cardiovascular dysfunction, impaired ventilatory function, cognitive impairment, increased pain perception, psychomotor disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 128 publications
0
1
0
Order By: Relevance
“…Furthermore, observational studies in humans have also shown delayed melatonin secretion and glucocorticoid release [ 23 ]. The potential disruption of the circadian timing system resulting from sleep irregularity during anesthesia may have a negative impact on human health and may hinder an individual’s ability to recover from surgery [ 24 ]. Female patients are more likely to report emotional distress prior to surgery, and in our previous research, they were more likely to report sleep disturbance over the following 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, observational studies in humans have also shown delayed melatonin secretion and glucocorticoid release [ 23 ]. The potential disruption of the circadian timing system resulting from sleep irregularity during anesthesia may have a negative impact on human health and may hinder an individual’s ability to recover from surgery [ 24 ]. Female patients are more likely to report emotional distress prior to surgery, and in our previous research, they were more likely to report sleep disturbance over the following 3 days.…”
Section: Discussionmentioning
confidence: 99%